2018
DOI: 10.1002/acp.3399
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of psychological and physical injury schemas in civil cases

Abstract: SummaryCivil plaintiffs often seek compensation for their psychological injuries. Yet little is known about jurors' preconceived notions (or schemas) for a prospective plaintiff's pain and suffering. The present studies examined (a) whether jurors have psychological injury schemas (Studies 1 and 2), (b) whether their existence and development vary by the type of civil case (Studies 1 and 2) or its severity (Study 2), and (c) how psychological injury schemas compare with physical injury schemas on a number of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In fact, research has identified the existence of a consistent, yet amorphous sexual violence schema. For instance, the severity of sexual violence (i.e., mild vs. severe) influenced perceptions of victim‐perpetrator relationships (i.e., only in mild cases did participants expect the offender to be an acquaintance) and injury to the victim (i.e., only in severe cases are victims likely to experience injury; Vallano & McQuiston, 2018). These results suggest that participants downplay the potential severity of the most frequent sexual violence type—acquaintance assaults (Seto et al, 2015).…”
Section: Sexual Violence Schemas and Biasmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, research has identified the existence of a consistent, yet amorphous sexual violence schema. For instance, the severity of sexual violence (i.e., mild vs. severe) influenced perceptions of victim‐perpetrator relationships (i.e., only in mild cases did participants expect the offender to be an acquaintance) and injury to the victim (i.e., only in severe cases are victims likely to experience injury; Vallano & McQuiston, 2018). These results suggest that participants downplay the potential severity of the most frequent sexual violence type—acquaintance assaults (Seto et al, 2015).…”
Section: Sexual Violence Schemas and Biasmentioning
confidence: 99%
“…Indeed, processing and interpretation of sexual violence crimes is heavily guided by schematic expectations. For example, when compared to schemas for other civil wrongs, sexual violence schemas contained a higher number of details pertaining to injury (with the exception of a car accident; Vallano & McQuiston, 2018). Unfortunately, it has long been recognized that there is limited research on jurors' memory (Levinson, 2007), and to our knowledge this limited field of research has not been extended to sexual violence.…”
Section: Consequences Of Schematic Expectationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Judges are also particularly skeptical of emotional damages, due to concerns over malingering and potentially excessive damage awards (Kritzer et al, 2014). Although there is very little research that specifically compares physical and emotional pain claims, relevant research that does exist demonstrated that mock jurors were more likely to think of physical injuries than emotional injuries when asked to list injuries that a typical person would suffer as a result of a variety of incidents that could lead to either civil or criminal litigation (e.g., car accidents, slip and falls, kidnappings, and sexual assaults; Hart et al, 1997; Vallano & McQuiston, 2018).…”
Section: Perceptions Of Painmentioning
confidence: 99%